Conversion of rice husk into fermentable sugar by two stage hydrolysis - Lim, Siew Eng (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Rice husks, a complex lignocellulosic biomass which comprised of high cellulose content (38-50%), hemicellulose (23-32%) and lignin (15-25%) possesses the potential to pursue as low cost feedstock for production of ethanol. Dilute sulfuric acid at concentration of 1, 2, 3 (%, v/v) were used for pretreatments at varied hydrolysis time (15-60 min) and enzymatic saccharification at range of 45-60C and pH 4.5-6.0 were evaluated for conversion of rice husk's cellulose and hemicellulose to fermentable sugars. The maximum yield of fermentable sugars from rice husks by dilute sulfuric acid (2%, 60 minutes) was 0.0751 g/l. Total fermentable sugar was identified using dinitrosalicylic acid (DNS) method and expressed in g/l. Enzymatic hydrolysis for conversion of cellulose to fermentable sugar has been studied by applying response surface methodology (RSM) and Analysis of Variance (ANOVA). Two independent variables namely initial pH and incubation temperature were considered using Central Composite Design (CCD). The determination coefficient, R2 obtained was 0.9848. This indicates that 98.48% capriciousness in the respond could be clarified by the ANOVA. Based on the data showed on Design Expert software, the optimum condition for total sugar production was at pH 6.0 and temperature 45C as it produced 0.5086 g/l of total sugar.